Urgensitas Kisah dalam Al-Qur’an - Suhaimi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Recently, the Indonesian people are often shocked by various natural events that have occurred in several parts of Indonesia. Uniquely, some of the series of events that occurred had happened to people before the Prophet Muhammad. and even then all have been covered in the al-Qur'an as the holy book of Muslims. The stories in the Al-Qur'an (Qasa> s al-Qur'a> n) are true stories in the Koran that have previously happened. This is intended to be an important lesson for Muslims as much as possible. If studied in-depth, there is a correlation between natural disasters that occurred and the stories contained in the Al-Qur'an. Therefore, in this article, we will discuss the urgency of the story in the Al-Qur'an in relation to natural disasters that occurred in Indonesia.